Curing the endogenous megaplasmid in Clostridium saccharoperbutylacetonicum N1-4 (HMT) using CRISPR-Cas9 and preliminary investigation of the role of the plasmid for the strain metabolism. (15th January 2019) - Gu, Yanyan; Feng, Jun; Zhang, Zhong-Tian; Wang, Shaohua; Guo, Liang; Wang, Yifen; Wang, Yi
Highlights: The endogenous megaplasmid was successfully cured with CRISPR-Cas9. Mutant strain has higher plasmid transformation efficiency and plasmid stability. The mutant strain produced slightly higher butanol and ABE than the control. The megaplasmid contributes to ester production in the wild type strain. Results provides insights into the function of the endogenous megaplasmid. Abstract: Clostridium saccharoperbutylacetonicum N1-4 (HMT) is known as a hyper acetone-butanol-ethanol (ABE) producing strain. Within its genome, there is an endogenous megaplasmid (Csp_135p) of 136 kb, which contains 104 protein-encoding genes and two pseudogenes. Till now, the function of the megaplasmid is unknown; meanwhile the existence of the megaplasmid could cause instability for the strain performance and barrier for efficient genome engineering. In order to investigate the function of the megaplasmid as related to ABE fermentation and other metabolisms, here we successfully eliminated the megaplasmid using the CRISPR-Cas9 system, generating the plasmid-null strain N1-4-C. Results from systematic characterization experiments indicated that the N1-4-C strain exhibited higher plasmid transformation efficiency and better plasmid stability than the N1-4 (HMT) strain. In addition, the N1-4-C strain could produce slightly higher concentration of butanol and ABE, along with more efficient re-assimilation of acids. Since there is a gene encoding a lipase on Csp_135p, we evaluated the capability for ester production of both N1-4-C and N1-4 (HMT) strains. Results demonstrated that the Csp_135p plasmid also contributed to the ester production (such as butyl acetate and butyl butyrate; this is the first report for ester production in C. saccharoperbutylacetonicum ) . This study demonstrated that the CRISPR-Cas9 system can be used as an efficient tool for the curing of endogenous plasmids. The plasmid-null N1-4-C strain can serve as a great platform for the development of more robust strains for biofuel and biochemical production.